2021
DOI: 10.1111/jace.17978
|View full text |Cite
|
Sign up to set email alerts
|

Toward understanding the reaction between silicon carbide and iridium in a broad temperature range

Abstract: The reaction between iridium and SiC in the 1000°C-1900°C temperature range was studied in details. The rate of this reaction was found to depend not only on temperature, but also on the grain sizes of the initial reagents, oxygen impurities in SiC, as well as the Ir: SiC ratio. The use of fine-grained initial reagents accelerates the reaction, whereas oxygen impurities in SiC powders slow it down. For the Ir: SiC ratio = 1:1, the IrSi silicide phase became dominant at 1400°C and remained the main phase at tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…An approach involving displacement of the interlayer between the carbon surface and iridium was proposed overcome this limitation 15 . It was suggested that the refractory carbides of group IV–V metals can be appropriate compounds for these purposes 16–19 . Indeed, refractory carbides react with iridium metal at temperatures above 1200°C to form MIr 3 intermetallics, which are thermodynamically and chemically stable and can act as coating materials for operation under extreme conditions 20–22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An approach involving displacement of the interlayer between the carbon surface and iridium was proposed overcome this limitation 15 . It was suggested that the refractory carbides of group IV–V metals can be appropriate compounds for these purposes 16–19 . Indeed, refractory carbides react with iridium metal at temperatures above 1200°C to form MIr 3 intermetallics, which are thermodynamically and chemically stable and can act as coating materials for operation under extreme conditions 20–22 .…”
Section: Introductionmentioning
confidence: 99%
“…15 It was suggested that the refractory carbides of group IV-V metals can be appropriate compounds for these purposes. [16][17][18][19] Indeed, refractory carbides react with iridium metal at temperatures above 1200 • C to form MIr 3 intermetallics, which are thermodynamically and chemically stable and can act as coating materials for opera-tion under extreme conditions. [20][21][22] Zirconium-containing refractory compounds are of special interest because they have an obvious advantage over hafnium-or tantalum analogs in terms of density.…”
Section: Introductionmentioning
confidence: 99%